STRATEGI PENGEMBANGAN USAHATANI CABAI BESAR (Capsicum annum L) DI KECAMATAN SOSOH BUAY RAYAP KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
This research was conducted in Sosoh Buay District of Ogan Komering Ulu District. The method used in this research is survey method. Sampling in this research using saturated sample method, sample taken from big chilli farmers in Sosoh Buay Termite Subdistrict. Data types used in this studyinclude primary and secondary data. The data processing method is using SWOT Matrix Analysis. Where Matrix SWOT is the merger of IFAS factor and EFAS factor to form a strategy. Based on the results of the research, it is found that the internal factors of the development of large chilli farming are by strength (having large land for chilli cultivation, fresh chillies are fresh, harvesting can be done more than once a year and related to health) and with weaknesses (farming technology still simple, non-durable products, farmer knowledge in big chilli farming is still low and lack of agroindustry factory). And the external factor of chili development is by chance (high consumer demand, broad marketing scale, superior commodities and government support), and with threats (pest and disease attacks on plants, fluctuating prices, and difficult adaptation to changing weather ). As well as the strategy of developing large chilli farms, SO strategy (increasing the production of large chilli by continuing to grow the area for large chilli cultivation, reducing the use of excessive chemical pesticides to produce better chilled fruit and maintain the production quality with proper care and cultivating chili fruit which is healthy to consume without excessive pesticides, ST strategies (preferably on the production quality with the proper application of integrated pest control), establish institutional interaction between chilli farmers by increasing the extension of large chilli farming and improving agricultural technology in pest and disease control, such as the use of pestona and natural glio), WO strategy (Chili farming technology is enhanced especially in land processing, such as the use of tractors, cultivators and rotavaltors to produce maximum production, post-harvest handling is specifically designed to minimize damage to chili, to cultivate superior seed varieties to produce chili fruits that can compete with imported chili and increase cooperation with the government to continue to develop large chilli farms in the hope that the government will provide funding to build agro-industry plants), and strategies WT (establishing a network of cooperation with the government, such as increasing the extension of the cultivation of chilli cultivation, maintaining the highest quality of production in order to be able to compete with the global marketplace and use superior seeds to produce quality production with better care).